Super-lubricity anticorrosive paint for overhead transmission conductor as well as preparation method and application of super-lubricity anticorrosive paint

By using ultra-slip anticorrosion coatings and anodizing technology on overhead transmission wires, the problems of short service life and poor anticorrosion effect in harsh environments are solved, and efficient anticorrosion and lubrication effects are achieved, extending the service life of the wire.

CN119529609APending Publication Date: 2025-02-28ELECTRIC POWER RESEARCH INSTITUTE OF STATE GRID SHANDONG ELECTRIC POWER COMPANY

Patent Information

Application Number
CN202411752839.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing overhead transmission conductors have a short service life in harsh environments, and the existing anticorrosion coatings have poor anticorrosion effects in high humidity environments, making it difficult to meet the needs of complex service conditions and high anticorrosion grades.

Method used

A super-slip anticorrosion coating for overhead transmission wires is adopted, and the composition includes polyvinyl fluoride resin, epoxy resin, fluorinated graphite, ultrafine alumina, zinc powder and zinc phosphate. Through surface modification and dynamic coating technology, a chemically inert film is formed on the surface of the filler, which reduces friction and forms an oxide film through anodization to enhance adhesion and corrosion resistance.

Benefits of technology

It significantly improves the corrosion resistance, lubricity and corrosion resistance of the coating, extends the service life of the wire, and maintains good corrosion resistance in high humidity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529609A_ABST
    Figure CN119529609A_ABST
Patent Text Reader

Abstract

The invention discloses a super-smooth anticorrosive coating for an overhead transmission conductor and a preparation method and application thereof.The super-smooth anticorrosive coating for the overhead transmission conductor is prepared from, by mass, 25-50 parts of polyvinyl fluoride resin, 12-50 parts of epoxy resin, 5-10 parts of butyl acetate, 5-10 parts of graphite fluoride, 5-8 parts of molybdenum disulfide, 5-20 parts of superfine aluminum oxide and 6-25 parts of zinc powder. And 1-12.5 parts of zinc phosphate. Surface modification and dynamic coating are carried out on the super-smooth filler particles, so that a layer of chemical inert film is formed on the surface of the filler, and the friction force between the particles and between the particles and a matrix is reduced. Meanwhile, a multi-stage dispersion technology is adopted, low-speed stirring is firstly carried out for primary mixing, and then gradual speed increasing is combined with ultrasonic treatment, so that aggregates of the filler can be fully destroyed, and a stable dispersion state is formed. The treatment can form a highly uniform super-lubricity network structure, improve the interface bonding between the filler and the matrix resin, reduce micropores in the coating and reduce the friction coefficient of the coating, so that the coating shows super-lubricity. And through ultrasonic oscillation treatment, preservative particles reach the nanoscale, the surface area and chemical activity of the particles are increased, the particles and matrix resin form more stable combination, and the anticorrosive effect of the coating is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to an ultra-slip anti-corrosion coating for overhead power transmission lines and a preparation method and application thereof. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] At present, overhead power transmission lines at home and abroad are mainly steel-core aluminum conductors, which are responsible for transmitting electrical energy from power sources to power load centers and occupy an extremely important position in transmission lines. With the rapid development of my country's economy and the acceleration of industrialization, the service environment of overhead power transmission lines has become increasingly complex and deteriorating. For example, under the influence of wind, frost and other harsh environmental factors, overhead power transmission lines will swing, causing micro-motion wear and micro-motion fatigue; under the influence of corrosive media such as moisture, chemical gases, dust and salt substances in the atmosphere, overhead power transmission lines will corrode, become significantly brittle, and their tensile strength will be greatly reduced. Therefore, accidents of overhead power transmission lines caused by corrosion occur from time to time. How to effectively improve the service life of aluminum conductors in harsh environments has become an important issue that needs to be solved urgently.

[0004] Anti-corrosion measures for overhead power transmission lines include coating with anti-corrosion grease, using alloy coatings, aluminum-clad steel materials, adopting new materials and processes, and optimizing conductor structure design. Surface functional coating anti-corrosion technology is seen as a promising solution, especially super-hydrophobic surface anti-corrosion. However, super-hydrophobic anti-corrosion technology shows limitations in high humidity environments, because water vapor will penetrate into its micro-nano voids to form an invisible water vapor film, resulting in anti-corrosion failure. To address this problem, in recent years, some researchers have proposed the concept of super-lubricating surface anti-corrosion, which fills the porous structure with a liquid lubricating layer to prevent water vapor from entering and prevent the formation of a water vapor film, thereby significantly improving the anti-corrosion effect. Therefore, in order to meet the complex service conditions and high anti-corrosion grade requirements, it is urgent to independently develop high-performance and economical overhead wire anti-corrosion coatings and products.

[0005] The invention patent with announcement number CN 109585055 A proposes an anti-corrosion conductor and its production process. The invention applies an anti-corrosion coating layer on the outside of the aluminum conductor. The anti-corrosion coating layer contains 70-85wt.% fluorinated acrylic acid mixed ester, 3-5wt.% inorganic pigment, 0.5-1.5wt.% wetting dispersant, 5-8wt.% photoinitiator and 10-20wt.% anhydrous butyl ester, which solves the problem of poor corrosion resistance of overhead conductors in corrosive environments. However, the service life of the coating in harsh environments such as high humidity needs to be improved, and only the anti-corrosion performance is mentioned, and other performances are not mentioned, so it is not suitable for promotion and application.

[0006] Prior art CN 117867553 A discloses a method for preparing a super-lubricating anti-icing aluminum wire. The invention uses an aluminum wire as an anode and a stainless steel plate as a cathode. The cathode and anode are connected to a DC power supply through a wire, and then placed in an electrolyte for anodization to obtain an anodized wire; the wire is immersed in a perfluorooctyltriethoxysilane-ethanol solution, and then placed in an oven for curing to obtain an anti-icing surface. The invention reduces the competitive reaction of chloride ions by regulating the concentration of chloride ions and glycerol, making it easier for aluminum ions to participate in the oxidation reaction, while improving the hardness and wear resistance of the oxide film layer. However, the electrolyte used in this invention is a phosphoric acid electrolyte. We have verified that under the same experimental parameters, the surface prepared using a phosphoric acid electrolyte has a larger pore size, and the corrosive medium is more likely to erode the sample substrate through the porous layer, which is not suitable for promotion and application. Summary of the invention

[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide an ultra-slip anti-corrosion coating for overhead power transmission lines and a preparation method and application thereof.

[0008] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0009] In a first aspect, the present invention provides an ultra-slip anti-corrosion coating for overhead transmission lines, which comprises the following components, measured by mass: 25-50 parts of polyvinyl fluoride resin, 15-50 parts of epoxy resin, 5-10 parts of butyl acetate, 5-10 parts of graphite fluoride, 5-8 parts of molybdenum disulfide, 5-20 parts of ultrafine alumina, 6-25 parts of zinc powder, and 1-12.5 parts of zinc phosphate.

[0010] The role of polyvinyl fluoride resin is to provide excellent chemical inertness, lubricity and corrosion resistance, and together with epoxy resin, provide balanced mechanical strength and adhesion to ensure the durability and super-slip performance of the coating;

[0011] The role of epoxy resin is to provide excellent adhesion and mechanical strength, make up for the disadvantage of low adhesion of PTFE, complement PTFE and improve the comprehensive performance of the coating;

[0012] Butyl acetate is used as a dispersant to reduce the mixing viscosity, help disperse the components evenly, and improve the processing performance and spraying effect of the coating;

[0013] The role of graphite fluoride is to improve the self-lubricating property and wear resistance of the coating, and together with PTFE, it enhances the lubrication effect and reduces the friction coefficient;

[0014] The role of molybdenum disulfide is to improve wear resistance and high temperature friction resistance, complementing graphite fluoride to further enhance the lubrication effect;

[0015] The role of ultrafine alumina is to improve the mechanical strength, wear resistance and stability of the coating, optimize the dispersion of fillers, and enhance the physical properties of the overall coating;

[0016] The role of zinc powder is to provide cathodic protection, enhance anti-corrosion performance, and combine with zinc phosphate to form an excellent anti-corrosion protective layer;

[0017] The function of zinc phosphate is to provide an anti-corrosion barrier, inhibit corrosion reactions on the metal surface, form synergistic protection with zinc powder, and extend the service life of the coating.

[0018] In addition, polyvinyl fluoride (PTFE) has excellent chemical inertness and lubricating properties, which can significantly enhance the corrosion resistance and lubricating properties of the coating. However, PTFE has low mechanical strength and poor adhesion, so epoxy resin is needed to provide good adhesion and mechanical strength. The ratio of 1:1-2:1 ensures that the performance of the two resins is complementary. A higher proportion of PTFE may result in insufficient adhesion, while a higher proportion of epoxy resin will reduce the lubricity of the coating.

[0019] In some embodiments, the ultra-slip anti-corrosion coating for overhead transmission lines comprises the following components, measured by mass: 25-45 parts of polyvinyl fluoride resin, 20-45 parts of epoxy resin, 5-10 parts of butyl acetate, 5-10 parts of graphite fluoride, 5-8 parts of molybdenum disulfide, 5-15 parts of ultrafine alumina, 6-25 parts of zinc powder, and 1-10 parts of zinc phosphate.

[0020] Preferably, the ultra-slip anti-corrosion coating for overhead transmission lines comprises the following components, measured by mass: 40 parts of polyvinyl fluoride resin, 20 parts of epoxy resin, 8 parts of butyl acetate, 8 parts of graphite fluoride, 6 parts of molybdenum disulfide, 10 parts of ultrafine alumina, 6 parts of zinc powder, and 2 parts of zinc phosphate.

[0021] In some embodiments, the particle size of the ultrafine alumina is 0.02-0.1 μm; the particle size of the zinc powder is 1-5 μm; and the particle size of the zinc phosphate is 0.5-2 μm.

[0022] In a second aspect, the present invention provides a method for preparing the ultra-slip anti-corrosion coating for overhead power transmission lines, comprising the following steps:

[0023] After the polyvinyl fluoride resin and the epoxy resin are uniformly mixed in proportion, butyl acetate is added and stirred at 40-60°C until a uniform semi-fluid dispersion is formed;

[0024] Adding graphite fluoride and molybdenum disulfide to the semi-fluid dispersion, premixing, shearing and dispersing, and adding ultrafine alumina in portions during the process to enhance the dispersion effect of the filler, to obtain a mixture;

[0025] The zinc powder and zinc phosphate are mixed, subjected to ultrasonic treatment to nano-size the mixture, and then added to the mixture under stirring to obtain the anti-corrosion coating.

[0026] The present invention forms a chemically inert film on the surface of the filler to reduce the friction between the particles and between the particles and the matrix by performing surface modification of the ultra-slip filler particles (adding a modifier to the dispersion, combining ultrasonic oscillation or wet treatment to allow the modifier to chemically bond with the particle surface to generate a film layer with chemical inertness and lubricity) and dynamic coating (using multi-stage dispersion, ultrasonic oscillation and other methods to gradually cover the particle surface with ultra-fine alumina, while the filler surface absorbs the dispersant and the matrix resin to form a stable coating structure, and curing at room temperature to ensure the durability and uniformity of the film layer).

[0027] The present invention adopts multi-stage dispersion technology, which helps to improve the uniformity of filler dispersion, enhance the adhesion and stability of the coating, and then improve the lubrication performance of the coating surface and enhance the corrosion resistance of the coating. In the low-speed stirring stage, polyvinyl fluoride resin, epoxy resin and other ingredients can be evenly mixed to avoid the formation of large agglomerates. Low-speed stirring helps to stabilize the dispersion system and prevent solvent volatilization or separation of coating components. In the high-speed stirring stage, the filler (such as graphite fluoride, molybdenum disulfide) in the system will be subjected to a strong shear force, further uniformly dispersed and refined to form a stable semi-fluid dispersion. This high-shear dispersion method can significantly improve the uniformity of the filler in the resin matrix and avoid particle sedimentation or stratification.

[0028] In some embodiments, the premixing time is 15-30 min, and the shear dispersion time is 30-45 min.

[0029] Preferably, the stirring speed of the premix is ​​300-500rpm; the stirring speed of the shear dispersion is 1500-2000rpm, and the stirring speed is gradually increased. The gradual increase in speed can avoid the problem of filler reagglomeration or stratification caused by excessive instantaneous shear force, and at the same time helps to prevent the solvent from volatile or bubble generation, ensuring the compatibility and stability between the filler and the resin, so that the final coating has better performance.

[0030] In some embodiments, the ultrasonic treatment time is 10-20 min.

[0031] In a third aspect, the present invention provides the use of the ultra-slip anti-corrosion coating for overhead power transmission lines in anti-corrosion treatment of overhead power transmission lines.

[0032] In a fourth aspect, the present invention provides an ultra-slip anti-corrosion coating for overhead power transmission lines, which is prepared from the ultra-slip anti-corrosion coating.

[0033] In some embodiments, the method for preparing the super-slip anti-corrosion coating for overhead power transmission wires comprises the following steps: anodizing the overhead power transmission wires to form an oxide film on the surface of the wires, then cleaning the wires to remove residual solution, and drying the wires;

[0034] The dried conductor is vacuum-impregnated in a silane coupling agent for a set time, and then the conductor is tilted to allow excess silane coupling agent to flow away, and the anti-corrosion coating is evenly coated on the surface of the conductor and cured to obtain the product.

[0035] Preferably, during anodization, the electrolyte is a 10-20 wt. % sulfuric acid solution, preferably a 15 wt. % sulfuric acid solution.

[0036] Preferably, the thickness of the oxide film is 5-10 μm. The thickness of the oxide film is required to be 5-10 μm because the oxide film in this thickness range is sufficient to provide good coating adhesion, and the microporous structure formed on the surface can provide more physical fitting points for the coating. Too thin an oxide film cannot provide sufficient protection and is easily corroded by the environment, while too thick a film will increase the brittleness of the material and may affect the mechanical properties of the conductor. In the application of power transmission lines, excessive film thickness may affect the flexibility and conductivity of the conductor, so a thickness of 5-10 μm provides a balance between performance and protection.

[0037] Preferably, the method for cleaning the wire is: placing the wire in anhydrous ethanol and ultrasonically cleaning it for 1-5 minutes.

[0038] Preferably, the drying process is carried out at a temperature of 70-90°C and for a time of 1-3 hours.

[0039] Preferably, the dried wire is vacuum impregnated in the silane coupling agent for 3-5 hours.

[0040] Preferably, the wire is inclined at an angle of 50-70°, preferably 60°.

[0041] Preferably, the thickness of the anti-corrosion coating applied on the surface of the conductor is 30-40 μm.

[0042] Preferably, the curing temperature is 20-40° C. and the curing time is 0.5-1.5 h.

[0043] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0044] The present invention forms a chemically inert film on the surface of the filler by surface modification and dynamic coating of the ultra-slip filler particles, thereby reducing the friction between the particles and between the particles and the matrix. At the same time, a multi-stage dispersion technology is adopted, which is initially mixed by stirring at a low speed, and then gradually increasing the speed in combination with ultrasonic treatment, so that the filler agglomerates can be fully destroyed and a stable dispersion state can be formed. This treatment can form a highly uniform ultra-slip network structure, improve the interface bonding between the filler and the matrix resin, reduce the micropores in the coating, and reduce the friction coefficient of the coating, so that it exhibits super-lubricating properties. Ultrasonic oscillation treatment is used to make the preservative particles reach the nanometer scale, increase the surface area and chemical activity of the particles, form a more stable bond with the matrix resin, and effectively improve the anti-corrosion effect of the coating.

[0045] The present invention adopts the method of combining anodization with coating. The oxide film formed by anodization provides adhesion and anti-corrosion performance for the coating, and can effectively improve the overall performance by combining with the super-slip coating. In addition, a 15wt.% H2SO4 solution is selected as the electrolyte for anodization, and the surface obtained has a porous structure, and its pore size is much smaller than that obtained by using phosphoric acid and oxalic acid as the electrolyte for anodization, and has a larger corrosion potential, which is 2 orders of magnitude and 1 order of magnitude smaller than the corrosion current density of oxalic acid and phosphoric acid samples, respectively, that is, the sample prepared by sulfuric acid electrolyte has better anti-corrosion performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0047] Figure 1 The microscopic morphology of the surface of the oxide film prepared in the sulfuric acid electrolyte in the embodiment of the present invention;

[0048] Figure 2 The scanning electron microscope image of the super-slip anti-corrosion coating in the embodiment of the present invention and the inset are schematic diagrams of static contact angles. DETAILED DESCRIPTION

[0049] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0050] The present invention will be further described below in conjunction with the embodiments.

[0051] In the embodiment, the prepared ultra-slip anti-corrosion coating is subjected to corrosion resistance testing on the coated test piece with reference to the provisions of standard GB / T 10125-2012 "Artificial atmosphere corrosion test salt spray test", and a neutral NaCl solution is used to accelerate corrosion and test by continuous spraying.

[0052] In accordance with GB / T 26490-2011 "Test Method for Super-amphiphobic Performance of Nanomaterials", the contact angle of the sample was tested using a contact angle meter. About 5 μL of deionized water was dropped on the sample surface using a micro-syringe. After it stabilized, optical photos were taken. Finally, semi-automatic fitting was performed using the elliptic differential method to calculate the contact angle between the water droplet and the sample surface.

[0053] The electrochemical test adopted a three-electrode system, with the experimental sample as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum electrode as the counter electrode. The electrochemical workstation (Chi760E, Shanghai Chenhua Instrument) was used to test at room temperature with 3.5wt.% NaCl solution as the corrosion solution. The contact area between the sample and the corrosion medium was 1cm 2 .

[0054] Example 1

[0055] Super-slip anti-corrosion coating I, by mass, includes the following components: 40 parts of polyvinyl fluoride resin, 20 parts of epoxy resin, 8 parts of butyl acetate, 8 parts of graphite fluoride, 6 parts of molybdenum disulfide, 10 parts of ultrafine aluminum oxide, 6 parts of zinc powder, and 2 parts of zinc phosphate.

[0056] The preparation method is as follows: polyvinyl fluoride resin and epoxy resin are mixed in a mass ratio of 2:1, butyl acetate is added, and the mixture is stirred at a low speed of 400 rpm and 45°C for 40 minutes to form a semi-fluid dispersion. Graphite fluoride and molybdenum disulfide are added, mixed at a low speed for 20 minutes, and dispersed at a high speed of 1500 rpm for 35 minutes, and ultrafine alumina is gradually added at the same time. Zinc powder and zinc phosphate are ultrasonically vibrated for 15 minutes, and then slowly added to the dispersion to obtain an ultra-slip anti-corrosion coating I.

[0057] The method for preparing the anti-corrosion coating using the super-slip anti-corrosion coating I is as follows:

[0058] (1) Place the overhead transmission aluminum conductor in a 15wt.% sulfuric acid electrolyte at 1.5A / dm 2 After treatment at the current density for 25 min, an oxide film with a thickness of 8 μm was obtained.

[0059] (2) The anodized aluminum wire was ultrasonically vibrated in anhydrous ethanol for 2 min to remove the residual solution and then placed in an oven at 80°C for 2 h.

[0060] (3) The dried aluminum wire is placed in a silane coupling agent and vacuum-impregnated in a vacuum drying oven for 4 hours.

[0061] (4) Take out the aluminum wire and place it at an angle of 60°. After the silane coupling agent on the surface flows away, use conventional spraying equipment to control the coating thickness to 35 μm to ensure uniform coverage.

[0062] (5) After coating, the coating was cured at room temperature for 1 hour to form an ultra-slip anti-corrosion coating I.

[0063] Example 2

[0064] The super-slip anti-corrosion coating II includes the following components by mass: 30 parts of polyvinyl fluoride resin, 30 parts of epoxy resin, 7 parts of butyl acetate, 7 parts of graphite fluoride, 6 parts of molybdenum disulfide, 12 parts of ultrafine aluminum oxide, 6 parts of zinc powder, and 2 parts of zinc phosphate.

[0065] The preparation method is as follows: polyvinyl fluoride and epoxy resin are mixed in a mass ratio of 1:1, stirred at 50°C and 300 rpm for 30 minutes to form a uniform dispersion. Graphite fluoride is first added, stirred at a low speed for 15 minutes, and then dispersed at a high speed of 2000 rpm for 45 minutes, and ultrafine alumina is gradually added. Zinc powder and zinc phosphate are treated under ultrasound for 20 minutes, and gradually added during stirring to obtain ultra-slip anti-corrosion coating II.

[0066] The method for preparing the anti-corrosion coating using the super-slip anti-corrosion coating II is as follows:

[0067] (1) Place the overhead transmission aluminum conductor in a 15wt.% sulfuric acid electrolyte at 1A / dm 2 After treatment at a current density of 30 min, an oxide film with a thickness of 7 μm was obtained.

[0068] (2) The anodized aluminum wire was ultrasonically vibrated in anhydrous ethanol for 2 min to remove the residual solution and then placed in an oven at 80°C for 2 h.

[0069] (3) The dried aluminum wire is placed in a silane coupling agent and vacuum-impregnated in a vacuum drying oven for 4 hours.

[0070] (4) Take out the aluminum wire and place it at an angle of 60°. After the silane coupling agent on the surface flows away, use conventional spraying equipment to control the coating thickness to 35 μm to ensure uniform coverage.

[0071] (5) After coating, it is cured at room temperature for 1 hour to form an ultra-slip anti-corrosion coating II.

[0072] Example 3

[0073] The super-slip anti-corrosion coating III includes the following components by mass: 40 parts of polyvinyl fluoride resin, 20 parts of epoxy resin, 6 parts of butyl acetate, 6 parts of graphite fluoride, 6 parts of molybdenum disulfide, 10 parts of ultrafine alumina, 10 parts of zinc powder, and 2 parts of zinc phosphate.

[0074] The preparation method is as follows: polyvinyl fluoride and epoxy resin are mixed in a ratio of 2:1, butyl acetate is added, and the mixture is stirred at 500 rpm for 35 minutes at 40°C. Graphite fluoride and molybdenum disulfide are mixed at a low speed for 25 minutes, sheared at a high speed of 1800 rpm for 30 minutes, and ultrafine alumina is gradually added. Zinc powder and zinc phosphate are ultrasonically treated for 10 minutes, and then slowly added and stirred to obtain ultra-slip anti-corrosion coating III.

[0075] The method for preparing the anti-corrosion coating using the super-slip anti-corrosion coating III is as follows:

[0076] (1) Place the overhead transmission aluminum conductor in a 15wt.% sulfuric acid electrolyte at 2A / dm 2 After treatment at a current density of 20 min, an oxide film with a thickness of 6 μm was obtained.

[0077] (2) The anodized aluminum wire was ultrasonically vibrated in anhydrous ethanol for 2 min to remove the residual solution and then placed in an oven at 80°C for 2 h.

[0078] (3) The dried aluminum wire is placed in a silane coupling agent and vacuum-impregnated in a vacuum drying oven for 4 hours.

[0079] (4) Take out the aluminum wire and place it at an angle of 60°. After the silane coupling agent on the surface flows away, use conventional spraying equipment to control the coating thickness to 35 μm to ensure uniform coverage.

[0080] (5) After coating, the coating was cured at room temperature for 1 hour to form an ultra-slip anti-corrosion coating III.

[0081] Example 4

[0082] The super-slip anti-corrosion coating IV includes the following components by mass: 37.5 parts of polyvinyl fluoride resin, 25 parts of epoxy resin, 5 parts of butyl acetate, 5 parts of graphite fluoride, 5 parts of molybdenum disulfide, 12 parts of ultrafine aluminum oxide, 8 parts of zinc powder, and 2.5 parts of zinc phosphate.

[0083] The preparation method is as follows: polyvinyl fluoride and epoxy resin are mixed in a mass ratio of 1.5:1, butyl acetate is used as solvent, and stirred at 350 rpm for 40 min at 45°C. Molybdenum disulfide is added, stirred at a low speed for 30 min, sheared at a high speed of 1500 rpm for 40 min, and aluminum oxide is gradually added. Zinc phosphate and zinc powder are ultrasonically treated for 15 min, and stirred after addition to obtain super-slip anti-corrosion coating IV.

[0084] The method for preparing the anti-corrosion coating using the super-slip anti-corrosion coating IV is as follows:

[0085] (1) Place the overhead transmission aluminum conductor in a 15wt.% sulfuric acid electrolyte at 1.8A / dm 2The current density was treated for 20 min to form an oxide film of 5 μm.

[0086] (2) The anodized aluminum wire was ultrasonically vibrated in anhydrous ethanol for 2 min to remove the residual solution and then placed in an oven at 80°C for 2 h.

[0087] (3) The dried aluminum wire is placed in a silane coupling agent and vacuum-impregnated in a vacuum drying oven for 4 hours.

[0088] (4) Take out the aluminum wire and place it at an angle of 60°. After the silane coupling agent on the surface flows away, use conventional spraying equipment to control the coating thickness to 35 μm to ensure uniform coverage.

[0089] (5) After coating, the coating was cured at room temperature for 1 hour to form an ultra-slip anti-corrosion coating IV.

[0090] Example 5

[0091] The super-slip anti-corrosion coating V comprises the following components, by mass: 30 parts of polyvinyl fluoride resin, 45 parts of epoxy resin, 6 parts of butyl acetate, 5 parts of graphite fluoride, 5 parts of molybdenum disulfide, 6 parts of ultrafine aluminum oxide, 7 parts of zinc powder, and 1 part of zinc phosphate.

[0092] The preparation method is as follows: polyvinyl fluoride and epoxy resin are mixed in a ratio of 1:1.5, stirred at 450 rpm for 30 min at 55°C, graphite fluoride is stirred at a low speed for 15 min, then high-speed shear dispersion is performed at 1700 rpm for 45 min, and ultrafine alumina is gradually added. Zinc powder and zinc phosphate are treated for 20 min, and the mixture is slowly added and stirred to obtain the ultra-slip anti-corrosion coating V.

[0093] The method for preparing the anti-corrosion coating using the super-slip anti-corrosion coating V is as follows:

[0094] (1) Place the overhead transmission aluminum conductor in a 15wt.% sulfuric acid electrolyte at 1.2A / dm 2 The current density was treated for 30 min to form an oxide film of 10 μm.

[0095] (2) The anodized aluminum wire was ultrasonically vibrated in anhydrous ethanol for 2 min to remove the residual solution and then placed in an oven at 80°C for 2 h.

[0096] (3) The dried aluminum wire is placed in a silane coupling agent and vacuum-impregnated in a vacuum drying oven for 4 hours.

[0097] (4) Take out the aluminum wire and place it at an angle of 60°. After the silane coupling agent on the surface flows away, use conventional spraying equipment to control the coating thickness to 35 μm to ensure uniform coverage.

[0098] (5) After coating, the coating was cured at room temperature for 1 hour to form an ultra-slip anti-corrosion coating V.

[0099] Example 6

[0100] The super-slip anti-corrosion coating VI includes the following components by mass: 44 parts of polyvinyl fluoride resin, 22 parts of epoxy resin, 6 parts of butyl acetate, 6 parts of graphite fluoride, 6 parts of molybdenum disulfide, 8 parts of ultrafine aluminum oxide, 6 parts of zinc powder, and 2 parts of zinc phosphate.

[0101] The preparation method is as follows: polyvinyl fluoride and epoxy resin are mixed in a ratio of 2:1, butyl acetate is added, and the mixture is stirred at 400 rpm for 35 minutes at 40°C. Molybdenum disulfide is first added and stirred at a low speed for 25 minutes, and then sheared at a high speed of 1900 rpm for 30 minutes, and aluminum oxide is added successively. Zinc powder and zinc phosphate that have been ultrasonically treated for 15 minutes are gradually added to the dispersion, and the ultra-slip anti-corrosion coating VI is obtained after being stirred evenly.

[0102] The method for preparing the anti-corrosion coating using the super-slip anti-corrosion coating VI is as follows:

[0103] (1) Place the overhead transmission aluminum conductor in a 15wt.% sulfuric acid electrolyte at 2A / dm 2 The current density was treated for 25 min to form an oxide film of 9 μm.

[0104] (2) The anodized aluminum wire was ultrasonically vibrated in anhydrous ethanol for 2 min to remove the residual solution and then placed in an oven at 80°C for 2 h.

[0105] (3) The dried aluminum wire is placed in a silane coupling agent and vacuum-impregnated in a vacuum drying oven for 4 hours.

[0106] (4) Take out the aluminum wire and place it at an angle of 60°. After the silane coupling agent on the surface flows away, use conventional spraying equipment to control the coating thickness to 35 μm to ensure uniform coverage.

[0107] (5) After coating, the coating was cured at room temperature for 1 hour to form an ultra-slip anti-corrosion coating VI.

[0108] Example 7

[0109] The super-slip anti-corrosion coating VII comprises the following components, calculated by mass: 35 parts of polyvinyl fluoride resin, 35 parts of epoxy resin, 8 parts of butyl acetate, 5 parts of graphite fluoride, 5 parts of molybdenum disulfide, 6 parts of ultrafine aluminum oxide, 8 parts of zinc powder, and 3 parts of zinc phosphate.

[0110] The preparation method is as follows: polyvinyl fluoride and epoxy resin are mixed in a ratio of 1:1, stirred at 350 rpm for 45 minutes at 50°C to form a uniform dispersion. Graphite fluoride is added, stirred at a low speed for 20 minutes, sheared at a high speed of 2000 rpm for 35 minutes, and aluminum oxide is gradually added. Zinc powder and zinc phosphate are ultrasonically treated for 10 minutes, added to the mixture and stirred evenly to obtain the ultra-slip anti-corrosion coating VII.

[0111] The method for preparing the anti-corrosion coating using the super-slip anti-corrosion coating VII is as follows:

[0112] (1) Place the overhead transmission aluminum conductor in a 15wt.% sulfuric acid electrolyte at 1.6A / dm 2 The current density was treated for 30 min to form an oxide film of 7 μm.

[0113] (2) The anodized aluminum wire was ultrasonically vibrated in anhydrous ethanol for 2 min to remove the residual solution and then placed in an oven at 80°C for 2 h.

[0114] (3) The dried aluminum wire is placed in a silane coupling agent and vacuum-impregnated in a vacuum drying oven for 4 hours.

[0115] (4) Take out the aluminum wire and place it at an angle of 60°. After the silane coupling agent on the surface flows away, use conventional spraying equipment to control the coating thickness to 35 μm to ensure uniform coverage.

[0116] (5) After coating, the coating was cured at room temperature for 1 hour to form an ultra-slip anti-corrosion coating VII.

[0117] Example 8

[0118] The ultra-slip anti-corrosion coating VIII comprises the following components, calculated by mass: 28 parts of polyvinyl fluoride resin, 42 parts of epoxy resin, 6 parts of butyl acetate, 6 parts of graphite fluoride, 6 parts of molybdenum disulfide, 8 parts of ultrafine aluminum oxide, 6 parts of zinc powder, and 4 parts of zinc phosphate.

[0119] The preparation method is as follows: polyvinyl fluoride and epoxy resin are mixed in a mass ratio of 1:1.5, stirred at 300 rpm for 30 minutes at 40°C, and uniformly dispersed. Graphite fluoride is mixed at a low speed for 30 minutes, sheared at a high speed of 1800 rpm for 40 minutes, and aluminum oxide is gradually added. Zinc powder and zinc phosphate are treated with ultrasonic vibration for 20 minutes, and then slowly added to obtain the ultra-slip anti-corrosion coating VIII.

[0120] The method for preparing the anti-corrosion coating using the super-slip anti-corrosion coating VIII is as follows:

[0121] (1) Place the overhead transmission aluminum conductor in a 15wt.% sulfuric acid electrolyte at 1A / dm 2 The current density was treated for 25 min to form an oxide film of 5 μm.

[0122] (2) The anodized aluminum wire was ultrasonically vibrated in anhydrous ethanol for 2 min to remove the residual solution and then placed in an oven at 80°C for 2 h.

[0123] (3) The dried aluminum wire is placed in a silane coupling agent and vacuum-impregnated in a vacuum drying oven for 4 hours.

[0124] (4) Take out the aluminum wire and place it at an angle of 60°. After the silane coupling agent on the surface flows away, use conventional spraying equipment to control the coating thickness to 35 μm to ensure uniform coverage.

[0125] (5) After coating, the coating was cured at room temperature for 1 hour to form an ultra-slip anti-corrosion coating VIII.

[0126] Comparative Example 1

[0127] The difference from Example 1 is that only the epoxy resin is replaced by polyvinyl fluoride resin, and the rest is the same as Example 1.

[0128] Comparative Example 2

[0129] The difference from Example 1 is that only the polyvinyl fluoride resin is replaced by epoxy resin, and the rest is the same as Example 1.

[0130] Comparative Example 3

[0131] The difference from Example 1 is that butyl acetate is omitted, and the rest is the same as Example 1.

[0132] Comparative Example 4

[0133] The difference from Example 1 is that the fluorinated graphite is replaced by ordinary graphite, and the rest is the same as Example 1.

[0134] Comparative Example 5

[0135] The difference from Example 1 is that the 15wt.% sulfuric acid electrolyte is replaced by a 15wt.% phosphoric acid electrolyte, and the rest is the same as Example 1.

[0136] According to the test method described above, the performance of the ultra-slip anti-corrosion coating prepared in each embodiment was tested. The performance test results are shown in Table 1.

[0137] Figure 1 The microscopic morphology of the surface of the oxide film prepared in sulfuric acid electrolyte in Example 1 is shown. From the figure, it can be observed that the small pore structure is evenly distributed on the surface of the coating. The pore size is small, and the overall structure presents a relatively dense porous structure, which can provide more surface area for the coating and increase the bonding strength between the coating and the substrate. In addition, due to the small pore size, the penetration of corrosive media can be effectively prevented, thereby improving the anti-corrosion performance.

[0138] Figure 2The scanning electron microscope image of the super-slip anti-corrosion coating prepared in Example 1 is shown. It can be seen that its surface has a continuous microstructure, forming a texture similar to "ridges" or "granules". This surface morphology enhances the super-lubricating properties of the coating, reduces the friction contact surface with external substances, and helps to reduce the friction coefficient. At the same time, the illustration shows that the static contact angle is 146°, indicating that the coating has good hydrophobic properties. The super-hydrophobic surface can effectively prevent the adhesion of water, thereby further improving the anti-corrosion performance.

[0139] From the performance test results, it can be concluded that the coating of Example 1 performs well in all indicators, especially in contact angle (148°), friction coefficient (0.08), wear resistance (2.5%), salt spray test time (1000h) and electrochemical impedance (1.2×107Ω·cm 2 ) and other aspects, all reached a high level. This shows that the coating of Example 1 has comprehensive advantages in terms of water resistance, lubricity, wear resistance and corrosion resistance, and is a more ideal choice. In other embodiments, the performance of Example 6 is also relatively outstanding, especially the contact angle (146°) and salt spray test time (950h), which performs well and is an alternative solution second only to Example 1.

[0140] Table 1 Coating performance test results

[0141]

[0142]

[0143] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An ultra-slip anti-corrosion coating for overhead power transmission lines, characterized in that: The invention comprises the following components by weight: 25-50 parts of polyvinyl fluoride resin, 12-50 parts of epoxy resin, 5-10 parts of butyl acetate, 5-10 parts of graphite fluoride, 5-8 parts of molybdenum disulfide, 5-20 parts of ultrafine alumina, 6-25 parts of zinc powder and 1-12.5 parts of zinc phosphate.

2. The super-slip anti-corrosion coating for overhead power transmission lines according to claim 1, characterized in that: The particle size of the ultrafine alumina is 0.02-0.1 μm; the particle size of the zinc powder is 1-5 μm; and the particle size of the zinc phosphate is 0.5-2 μm.

3. The method for preparing the super-slip anti-corrosion coating for overhead power transmission lines according to claim 1 or 2, characterized in that: The steps include: After the polyvinyl fluoride resin and the epoxy resin are uniformly mixed in proportion, butyl acetate is added and stirred at 40-60°C until a uniform semi-fluid dispersion is formed; Adding graphite fluoride and molybdenum disulfide to the semi-fluid dispersion, premixing, shearing and dispersing, and adding ultrafine alumina in portions during the process to enhance the dispersion effect of the filler, to obtain a mixture; The zinc powder and zinc phosphate are mixed, subjected to ultrasonic treatment to nano-size the mixture, and then added to the mixture under stirring to obtain the anti-corrosion coating.

4. The method for preparing the super-slip anti-corrosion coating for overhead power transmission lines according to claim 3, characterized in that: The premixing time is 15-30 minutes, and the shear dispersion time is 30-45 minutes; Preferably, the stirring speed of the premixing is 300-500 rpm; the stirring speed of the shear dispersion is 1500-2000 rpm, and the stirring speed is gradually increased.

5. The method for preparing the super-slip anti-corrosion coating for overhead power transmission lines according to claim 3, characterized in that: The ultrasonic treatment time is 10-20 min.

6. Use of the super-slip anti-corrosion coating for overhead power transmission lines according to claim 1 or 2 in anti-corrosion treatment of overhead power transmission lines.

7. An ultra-slip anti-corrosion coating for overhead power transmission lines, characterized in that: Prepared from the ultra-slip anti-corrosion coating according to claim 1 or 2.

8. The method for preparing the super-slip anti-corrosion coating for overhead power transmission lines according to claim 7, characterized in that: The method comprises the following steps: performing anodizing treatment on the overhead transmission wire to form an oxide film on the surface of the wire, then cleaning the wire to remove the residual solution, and performing drying treatment; The dried conductor is vacuum-impregnated in a silane coupling agent for a set time, and then the conductor is tilted to allow excess silane coupling agent to flow away, and the anti-corrosion coating is evenly coated on the surface of the conductor and cured to obtain the product.

9. The method for preparing the super-slip anti-corrosion coating for overhead power transmission lines according to claim 8, characterized in that: When anodizing, the electrolyte is a 10-20wt% sulfuric acid solution, preferably a 15wt.% sulfuric acid solution; Preferably, the thickness of the oxide film is 5-10 μm; Preferably, the method for cleaning the wire is: placing the wire in anhydrous ethanol and ultrasonically cleaning it for 1-5 minutes.

10. The method for preparing the super-slip anti-corrosion coating for overhead power transmission lines according to claim 8, characterized in that: The drying temperature is 70-90°C and the drying time is 1-3h; Preferably, the dried wire is vacuum impregnated in the silane coupling agent for 3-5 hours; Preferably, the wire is tilted at an angle of 50-70°, preferably 60°; Preferably, the thickness of the anti-corrosion coating applied on the surface of the conductor is 30-40 μm; Preferably, the curing temperature is 20-40° C. and the curing time is 0.5-1.5 h.

Citation Information

Patent Citations

  • Anti-corrosion wire and production process thereof

    CN109585055A

  • Preparation method of super-lubricating anti-icing aluminum conductor

    CN117867553A

  • Nanocomposite coatings for threaded connections

    CN101657668A

  • Swash plate based on cyanate

    CN103881560A

  • Production method of combination of aluminium alloy and resin

    CN104962972A

Cited By

  • Flame-retardant heat-insulating coating for battery compartment and preparation method of flame-retardant heat-insulating coating

    CN121736623A